2004
DOI: 10.1021/pr049916l
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Gastric Cancer Metastasis by Two-Dimensional Gel Electrophoresis and Matrix Assisted Laser Desorption/Ionization-Mass Spectrometry for Identification of Metastasis-Related Proteins

Abstract: A well-described animal model was used to understand the molecular mechanisms of carcinogenesis and metastasis of gastric cancer at the protein level. Gastric cancer was induced in 12 Wistar rats by oral administration of N-methyl-N'-Nitro-N-Nitrosoguanidine (MNNG). The protein expression patterns of normal gastric tissue, gastric cancer, and corresponding metastases were analyzed by proteomics in matched tissues of 3 rats. Proteins in the region of molecular masses of 15-75 kDa and an isoelectric point of 3-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…The over-expression of HSP27 in gastric cancer has been observed by several studies (8,25,26). In gastric cancer, over-expression of HSP27 may be associated with metastasis to the lymph nodes, advanced stage (III and IV) cancer, and shorter overall survival of patients (27,28), indicating that HSP27 has prognostic significance for gastric cancer.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The over-expression of HSP27 in gastric cancer has been observed by several studies (8,25,26). In gastric cancer, over-expression of HSP27 may be associated with metastasis to the lymph nodes, advanced stage (III and IV) cancer, and shorter overall survival of patients (27,28), indicating that HSP27 has prognostic significance for gastric cancer.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, HSP27 expression was closely related to gastric tumor size, and the presence of organ metastases (29). However, another study found that HSP27 was not present in metastatic gastric tumors, and was only detectable in samples from non-metastatic gastric cancer tissue (26). None of these studies measured HSP27 serum concentrations to investigate if there is a link between intracellular and extracellular HSP27 concentrations in gastric neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…These conflicting results may suggest that shock protein abundance varies in different stages of gastric cancer, which needs further study. Chen et al (23) reported that HSP27 was expressed in human gastric cancer, whereas non-tumorous, non-regenerative human foveolar epithelium did not express HSP27. In our research, HSP27 was down-regulated on DIGE.…”
Section: Discussionmentioning
confidence: 99%
“…In primary breast cancer samples, DJ-1 negatively regulates the PTEN tumor suppressor and thus produces overexpressed hyperphosphorylation of PKB/Akt and increased cell survival (27 ). In a proteomic analysis of gastric cancer, DJ-1 was detectable only in metastatic tumor tissue vs nonmetastatic tumor tissue and healthy gastric tissue (28 ). Based on this fact, it seems likely that DJ-1 contributes to the metastatic potential of a tumor.…”
Section: Discussionmentioning
confidence: 99%